2017
DOI: 10.1021/jacs.7b01814
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly Can Direct Dynamic Covalent Bond Formation toward Diversity or Specificity

Abstract: With the advent of reversible covalent chemistry the study of the interplay between covalent bond formation and noncovalent interactions has become increasingly relevant. Here we report that the interplay between reversible disulfide chemistry and self-assembly can give rise either to molecular diversity, i.e., the emergence of a unprecedentedly large range of macrocycles or to molecular specificity, i.e., the autocatalytic emergence of a single species. The two phenomena are the result of two different modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 67 publications
(124 reference statements)
1
65
0
Order By: Relevance
“…Conjugates of the 3,5‐dimercaptobenzoic acid and peptides designed to form the β‐sheet present a tendency to form oligomers from hexa‐ to octamers, which aggregate giving fibrillar structures . On the other hand, amphiphilic conjugates of the 1,3‐dimercaptophenyl moiety and oligo(ethylene oxide) show a preference to form the most fitted trimers and tetramers and, in a significantly smaller amount, also larger macrocycles up to 44‐mers . Creation of such large macrocyclic structures was explained by formation of intermediating aggregates of trimers and tetramers caused by the hydrophobic interactions of aryl scaffolds, and the following metathesis of disulfide bonds in such aggregates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugates of the 3,5‐dimercaptobenzoic acid and peptides designed to form the β‐sheet present a tendency to form oligomers from hexa‐ to octamers, which aggregate giving fibrillar structures . On the other hand, amphiphilic conjugates of the 1,3‐dimercaptophenyl moiety and oligo(ethylene oxide) show a preference to form the most fitted trimers and tetramers and, in a significantly smaller amount, also larger macrocycles up to 44‐mers . Creation of such large macrocyclic structures was explained by formation of intermediating aggregates of trimers and tetramers caused by the hydrophobic interactions of aryl scaffolds, and the following metathesis of disulfide bonds in such aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…[12,16,44] On the other hand, amphiphilic conjugates of the 1,3-dimercaptophenylm oiety ando ligo(ethylene oxide) show ap reference to formt he most fitted trimers and tetramers and, in as ignificantly smaller amount, also larger macrocycles up to 44-mers. [48] Creation of such large macrocyclics tructures was explained by formation of intermediating aggregates of trimers and tetramers caused by the hydrophobic interactions of aryl scaffolds, and the following metathesis of disulfide bonds in such aggregates. Nonetheless, trimeric and tetrameric structures were the most abundantf orm in these dynamic combinatorial libraries (DCLs).…”
Section: Oxidation Of Peptide Conjugatesmentioning
confidence: 99%
“…Interestingly,w hen the same experiment was repeated, but the mixture was not agitated following the addition of effector 3 the most abundant 1-containing species were 1 3 and 1 4 , which are also the main products in an on-agitated DCL prepared from 1 only ( Figure 1B). [13] These results show that upon addition of 3,the host-guest complex 2 4 ·3 is formed first, accompanied by the buildup of arange of 1-only oligomers.It also shows that in the coupled subsystems the emergence of the replicator is promoted by mechanical agitation, as is the case for the separate replication subsystem.…”
mentioning
confidence: 77%
“…[13] In the DCL composed of building blocks 2 and 4,addition of 3 triggered the exclusive formation of replicator 4 4 ( Figure 4B). [13] In the DCL composed of building blocks 2 and 4,addition of 3 triggered the exclusive formation of replicator 4 4 ( Figure 4B).…”
mentioning
confidence: 99%
“…Recently we reported that in disulfide-based [12] dynamic combinatorial libraries of dithiol building block 1 (Scheme 1) stirring induces the emergence of as elf-replicator (see the Supporting Information (SI), Figure S66) in the form of the cyclic hexamer (1 6 ), self-assembling first into nanoribbons, then transforming into nanoplatelets. [13] We set out to couple Scheme 1. Dynamic combinatorialc hemistry of asystem made from building blocks 1 and 2 and guest 3.…”
mentioning
confidence: 99%